2016
DOI: 10.1002/cam4.914
|View full text |Cite
|
Sign up to set email alerts
|

Risk of skeletal related events among elderly prostate cancer patients by site of metastasis at diagnosis

Abstract: The purpose of this study was to estimate the risk of developing skeletal‐related events (SREs) based on site of metastasis at diagnosis and identify other predictors of developing SREs among metastatic prostate cancer patients. We conducted a retrospective cohort study using linked SEER (Surveillance, Epidemiology, and End Results) and Medicare data and identified men over the age of 65 with incident metastatic prostate cancer diagnosed during 2005–2009. SREs included radiation (RAD), pathological fractures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…A study using linked data from the Surveillance, Epidemiology, and End Results program and Medicare examined the risk of SRE development depending on metastatic site . In a cohort of men with metastatic disease, they found that patients with metastases in the bone and lymph nodes, bone and “other” sites (including visceral metastases) with or without lymph nodes, and “other” sites only (including visceral metastases) were as likely as patients with bone metastases only to develop SREs . It is important to note that in the current study, only 44 men (5%) within the mCRPC cohort had visceral metastases at the time of their bone metastasis diagnosis, and despite these small numbers, we did note a significant association.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…A study using linked data from the Surveillance, Epidemiology, and End Results program and Medicare examined the risk of SRE development depending on metastatic site . In a cohort of men with metastatic disease, they found that patients with metastases in the bone and lymph nodes, bone and “other” sites (including visceral metastases) with or without lymph nodes, and “other” sites only (including visceral metastases) were as likely as patients with bone metastases only to develop SREs . It is important to note that in the current study, only 44 men (5%) within the mCRPC cohort had visceral metastases at the time of their bone metastasis diagnosis, and despite these small numbers, we did note a significant association.…”
Section: Discussionmentioning
confidence: 62%
“…Second, patients with visceral metastases within 1 month before or after bone metastasis diagnosis were more likely to develop an SRE compared with those without visceral metastases (HR, 1.91; 95% CI, 1.18‐3.09). A study using linked data from the Surveillance, Epidemiology, and End Results program and Medicare examined the risk of SRE development depending on metastatic site . In a cohort of men with metastatic disease, they found that patients with metastases in the bone and lymph nodes, bone and “other” sites (including visceral metastases) with or without lymph nodes, and “other” sites only (including visceral metastases) were as likely as patients with bone metastases only to develop SREs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported an increased risk of death in patients with bone + NRLN metastases compared to patients with only bone metastases (HR 1.37, 95% CI 1.17–1.6) for the overall cohort after adjusting for treatment received, baseline pain, Karnofsky performance score, prior progression type, PSA, tumour grade, alkaline phosphatase level and haemoglobin level. Furthermore, a recent SEER Medicare analysis of 4 404 patients with mPCa was conducted to evaluate the relationship of metastatic sites to skeletal‐related events . This study reported that patients with bone + NRLN metastases have a higher probability of developing skeletal‐related events compared with patients with only bone metastases (52% vs 46%).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid increase of its incidence and mortality rate, more and more patients are suffering from the associated emotional and physical burden, and the mortality rate of prostate cancer is second only to lung cancer34: because of the high progression, invasion, and metastasis rates of prostate cancer, it causes the highest mortality rate and has the lowest survival rate567. Prostate cancer threatens male health at all times8.…”
mentioning
confidence: 99%